Comparative Immunogenicity and Safety Trial of 2 Different Schedules of Single-visit Intradermal Rabies Postexposure Vaccination. (19th December 2018) - Soentjens, Patrick; De Koninck, Katrien; Tsoumanis, Achilleas; Herssens, Natacha; Van Den Bossche, Dorien; Terryn, Sanne; Van Gucht, Steven; Van Damme, Pierre; Van Herrewege, Yven; Bottieau, Emmanuel
Abstract: Background: Effective and safe single-visit rabies vaccination for pre- and postexposure prophylaxis (PrEP and PEP) could substantially simplify rabies prevention and therefore increase compliance. Methods: In a comparative trial, 303 healthy adults received a primary vaccination that consisted of 2 intradermal (ID) doses of 0.1 mL of the purified chicken embryo cell vaccine (PCEV) during a single visit. One year later, participants were randomly assigned to receive either 4 or 2 ID PEP booster doses of 0.1 mL PCEV during a single visit. The primary endpoint for immunogenicity was the percentage of participants with an adequate antibody level (>0.5 IU/mL) 7 days after the booster doses. The safety endpoint was the proportion of participants who developed adverse events (AEs) following primary and/or booster vaccination. Results: All participants, except 1 (99.3%) in each study group, had a rabies antibody titer >0.5 IU/mL on day 7 following the booster schedules. Participants exposed to the 4-dose PEP schedule had a geometric mean titer of 20 IU/mL vs 14 IU/mL for the 2-dose PEP schedule ( P = .0228). Local reactions at the injection site following PrEP and PEP were mild and transient and only seen in 14.9% and 49.6%–53% of the participants, respectively. No serious AEs were reported. Conclusions: In healthy adults, a 2-dose (2 × 0.1 mL) single-visit ID PEP schedule was as immunologically adequate and safe as a 4-dose (4 × 0.1 mL) single-visit PEP schedule 7 to 28 months following a 2-dose (2 × 0.1 mL) single-visit ID PREP. Clinical Trials Registration: EudraCT 2014-00183612. Abstract : In healthy adults, post-exposure prophylaxis consisting of a 2-dose single-visit intradermal rabies vaccination was as immunologically adequate and safe as a 4-dose single-visit vaccination following a 2-dose single-visit pre-exposure prophylaxis regimen 7 to 28 months earlier.